Theoretical-practical articulation of the continuous learning of leadership in Nursing in light of Peter Senge - Ises Adriana Reis dos Santos; Simone Coelho Amestoy; Gilberto Tadeu Reis da Silva; Vânia Marli Schubert Backes; Cristiane Costa Reis da Silva; Marimeire Morais da Conceição; Rebecca Maria Oliveira de Góis (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the theoretical-practical articulation of the continuous learning of leadership in undergraduate Nursing. Methods: Case study carried out at a Northeast federal public university. For data collection, semi-structured interview techniques, workshops, and document analysis were applied. Forty Nursing students participated in the interviews, and 26 in the workshops. The data were submitted to Minayo's operative analysis using the Nvivo software. Peter Senge's concepts were adopted. Results: The students demonstrated a greater understanding of the theme throughout the course and recognized contributing elements to the continuous learning of leadership, such as behavioral characteristics and the use of methodological approaches integrated with theoretical and practical spaces. Final considerations: The teaching of leadership is relevant in Nursing education, and this has been recognized by students, but still requires changes for it to become operational, with an improvement and a theoretical-practical integration of the cultivated experiences, suitable to the reality of the craft.